Knowledge and Attitude of Nurses on Implementation of Atraumatic Care among Hospitalized Children in Eastern Nepal: A Cross-sectional Study - Mahato, Pramila; Shrestha, Rit; Karn, Basant Kumar; Chaudhary, Amit Kumar; Singh, Rakesh (Journal of Nepal Paediatric Society, 2022)
Introduction: The modality and quality of care received during hospitalization affects a child’s response to their illness. Thus, any intervention delivered by healthcare providers including nurses must be based on principles of atraumatic care. This study aims to assess the knowledge and attitude of nurses in the implementation of atraumatic care among hospitalized children in a tertiary care center in Eastern Nepal. Methods: A descriptive cross-sectional study was conducted among 106 nurses in a tertiary hospital from 4th January to 1st February 2020. Ethical approval was received from the Institutional Review Committee. Sampling was done by total population enumeration method. Data was collected using a self-administered three-part questionnaire and analyzed using Statistical Package for the Social Sciences version 11.5 by utilizing descriptive statistics. Results: The mean knowledge and attitude of nurses towards implementation of atraumatic care among hospitalized children was found to be 14.90 ± 3.90 and 74.74 ± 7.5 respectively. Out of 106 nurses, 73 (68.90%) had adequate knowledge whereas 56 (52.80%) had favorable attitudes towards principles and implementation of atraumatic care, assessed using reliable scales. Variations due to socio-demographic and professional parameters were insignificant. Conclusions: The study shows that majority of the surveyed nurses had adequate knowledge of the principles of atraumatic care and a favorable attitude towards its application among hospitalized children. However, the measured attitude of nursing practitioners was relatively lower in terms of favorability.